Line and Color Composition in Lurik Cawas Weaving: Idea from Traditional Lurik Patterns - Widiastuti, Theresia; Rizali, Nanang; Anantanyu, Sapja; Waluyo, Sugeng Edi (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
Javanese lurik is weaved fabric with striped motives, and it has very simple appearance. In the past, lurik only used two colors, namely: black and white. But, as it develops, some of lurik fabrics use more than two colors, and one of the colors usually still consists of black or white color. After lurik becomes one of the prosper trading commodities, the artisans attempt to make lurik more appealing and varying in term of appearance so that it will be favored by consumers. The objective of this research is to investigate how the artisans can develop lurik patterns to stay appealing. This paper used the qualitative research with the case study strategy and phenomenological approaches. The study aims at understanding the methods employed by artisans in Cawas Klaten in developing lurik patterns. The result of the study show that (1) lurik pattern has been developed by using various alternatives of line composition and color coherence; (2) the idea of development comes from traditional lurik patterns which already existed long time ago; and (3) line and color composition used a minimum of three colors so that it looks like a rainbow, and this kind of lurik pattern becomes the characteristic of modern weaved fabric from Cawas.